Exploring Gender and Sikh Traditions - Jakobsh, Doris R. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume gathers scholars who focus on gender through a variety of disciplines and approaches to Sikh Studies. The intersections of religion and gender are here explored, based on an understanding that both are socially constructed. Far from being static, as so often presented in world religions textbooks, religious traditions are constantly in flux, responding to historical, cultural and social contexts. So too is 'the' Sikh tradition in terms of practices, ideologies, rituals, and notions of identity. We here conclude that 'a' Sikh tradition does not exist; instead, there are numerous forms thereof. In this volume, Sikhism is presented as a collection of 'Sikh traditions'. Gender studies-in line with women's liberation, masculine and feminist studies have long examined and have long deconstructed the patriarchy, but also move to identify other subordinate-dominant relations between individuals. Indeed, there are numerous forms of discrimination and power structures that simultaneously create a multiplicity of oppression. Intersectionality has become the basis of an increasingly systematized production of contemporary discourses on feminism and gender analysis, as is evidenced by the varied contributions in this volume.